An Exploration of the Perception of Dance and Its Relation to Biomechanical Motion: A Systematic Review and Narrative Synthesis. Issue 3 (September 2016) - Chang, Michael; Halaki, Mark; Adams, Roger; Cobley, Stephen; Lee, Kwee-Yum; O'Dwyer, Nicholas
In dance, the goals of actions are not always clearly defined. Investigations into the perceived quality of dance actions and their relation to biomechanical motion should give insight into the performance of dance actions and their goals. The purpose of this review was to explore and document current literature concerning dance perception and its relation to the biomechanics of motion. Seven studies were included in the review. The study results showed systematic differences between expert, non-expert, and novice dancers in biomechanical and perceptual measures, both of which also varied according to the actions expressed in dance. Biomechanical and perceptual variables were found to be correlated in all the studies in the review. Significant relations were observed between kinematic variables such as amplitude, speed, and variability of movement, and perceptual measures of beauty and performance quality. However, in general, there were no clear trends in these relations. Instead, the evidence suggests that perceptual ratings of dance may be specific to both the task (the skill of the particular action) and the context (the music and staging). The results also suggest that the human perceptual system is sensitive to skillful movements and neuromuscular coordination. Since the value perceived by audiences appears to be related to dance action goals and the coordination of dance elements, practitioners could place a priority on development and execution of those factors.